1992
DOI: 10.1111/j.1439-0434.1992.tb01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Activities of Trichoderma harzianum Against Pythium aphanidermatum and Pythium myriotylum on Tobacco

Abstract: Trichoderma harzianum rendered Pythium aphanidermatum and P. myriotylum non‐viable in Petri dish dual culture. The Pythium mycelia from such cultures showed natural autofluorescence in the regions of interactions, indicating their death. Non‐volatile and volatile fungicidal activities were detected in T. harzianum culture. Lytic activity of β‐(l,3)‐glucanase was detected on the cell walls of the Pythium spp. There was a significant decrease in the disease incidence when T. harzianum was incorporated into steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The supernatant was again centrifuged at 10 0006g for 10 min. The clear supernatant was collected and immediately used for electrophoresis (Devaki 1991;Fathima et al 2004). Part of the supernatant was stored at 08C for subsequent use.…”
Section: Extraction Of Soluble Mycelial Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was again centrifuged at 10 0006g for 10 min. The clear supernatant was collected and immediately used for electrophoresis (Devaki 1991;Fathima et al 2004). Part of the supernatant was stored at 08C for subsequent use.…”
Section: Extraction Of Soluble Mycelial Proteinsmentioning
confidence: 99%
“…E-mail: sbsarpangala@hotmail.com Archives of Phytopathology and Plant Protection May 2009;42(5): 489 -498 Protein and enzyme patterns from mycelial extract were extensively studied in various fungi (Clare & Zentmyer 1966;De Vallavieille & Erselius 1984;Rajamannar et al 2000;Mohammadi et al 2004). Electrophoretic protein profiling of mycelial proteins was employed by several authors to differentiate many species and sub-species of fungi (Ho & Jong 1987;Bielenin et al 1988;Devaki 1991;Brun et al 1997;Aggarwal et al 2001). Identification and classification of strains and races of fungi were done utilizing electrophoretic technique of soluble proteins (Burdon & Marshall 1981;Desai et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that large part of research works was conducted only under laboratory conditions or in vase experiments using sterilised soil or artificial mediums (Gilbert et al 1990;Smith et al 1993;Chen et al 1996;Okamoto et al 1998;Picard et al 2000a,b;Timmusk et al 2009;Logeshwaran et al 2011). The results obtained under laboratory conditions are not always identical with the ones obtained under in vivo conditions, which was illustrated by the studies carried out by Devaki et al (1992). The researchers proved high antagonistic effects of Trichoderma harzianum synthesising β-(l,3)glucanases on the growth of mycelium of Py.…”
Section: Biological Control Of Blight Diseases Caused By the Oomycetementioning
confidence: 95%
“…Cell wall degrading enzymes (CWDEs) such as chitinase, glucanase, and proteases are thought to be closely related to the mycoparasitism of Trichoderma strains [18, 23,24]. Inhibitory volatile substances such as alkylpyrons may also contribute to the biocontrol activity of some Trichoderma strains [25][26][27]. Harman et al [28] reported that the Trichoderma have the ability to antagonized soilborne phytopathogens as well as it also induced plant growth promotion and protect plants from biotic and abiotic stresses [29].…”
Section: Screening Of the Antagonistic Trichoderma Strainsmentioning
confidence: 99%